2023
DOI: 10.1186/s12967-023-04638-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-100a-5p-enriched exosomes derived from mesenchymal stem cells enhance the anti-oxidant effect in a Parkinson’s disease model via regulation of Nox4/ROS/Nrf2 signaling

Songzhe He,
Qiongqiong Wang,
Liankuai Chen
et al.

Abstract: Background The pathogenesis of Parkinson's disease (PD) has not been fully elucidated, and there are no effective disease-modifying drugs for the treatment of PD. Mesenchymal stem cells have been used to treat several diseases, but are not readily available. Methods Here, we used phenotypically uniform trophoblast stage-derived mesenchymal stem cells (T-MSCs) from embryonic stem cells, which are capable of stable production, and their exosomes (T-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…These exosomes contribute to the maintenance of nigrostriatal system function, improvement of motor impairments, and reduction of oxidative stress by the regulation of the NADPH oxidase 4 (Nox4)-ROS-Nrf2 axis (Fig. 1 ) [ 199 ].…”
Section: Neurological Injurymentioning
confidence: 99%
“…These exosomes contribute to the maintenance of nigrostriatal system function, improvement of motor impairments, and reduction of oxidative stress by the regulation of the NADPH oxidase 4 (Nox4)-ROS-Nrf2 axis (Fig. 1 ) [ 199 ].…”
Section: Neurological Injurymentioning
confidence: 99%
“…The T-MSC-EVs were found to directly target the 3' untranslated region of the NOX4 gene. This specific targeting mechanism was shown to provide neuroprotection against the degeneration of dopamine neurons, maintain the integrity and functionality of the nigrostriatal pathway, reduce motor impairments, and decrease oxidative stress via the Nox4-ROS-Nrf2 signaling pathway in PD models 63 . Accumulating evidences have shown that treatment with MSC-derived EVs markedly ameliorated in vivo ischemia/reperfusion brain injury, enhanced neuron viability in vitro, and reduced apoptosis.…”
Section: The Functions Of Native Sc-evsmentioning
confidence: 99%